Pengelolaan Sarana dan Prasarana pada Sekolah Indonesia Luar Negeri - Randi Hendriansyah; Erny Roesminingsih; Yatim Riyanto; Amrozi Khamidi; Mochamad Nursalim (LP. Ma'arif Janggan Magetan, 2024)
This research aims to describe the management of facilities and infrastructure at SILN (Sekolah Indonesia Luar Negeri) Kota Kinabalu Sabah Malaysia. The research method used is qualitative with a phenomenological approach, which takes primary data from in-depth interviews with informants regarding their experience in managing facilities and infrastructure as well as direct observations in the field, triangulation of sources and techniques is also carried out to test the validity of the data. The research results show that the management of facilities and infrastructure at SIKK (Sekolah Indonesia Kota Kinabalu) is carried out procedurally, management adapts to various conditions abroad (Malaysia) which are economically and slightly different in terms of economics and policies, acculturation of bureaucratic flows and foreign and domestic policies is needed. This research found that the management of facilities and infrastructure at SILN is slightly different from the management of facilities and infrastructure at State Schools in Indonesia. In conclusion, the management of facilities and infrastructure at SILN Kota Kinabalu Sabah Malaysia has its own challenges related to policy, bureaucracy and economic conditions